Kiwi OmniCup versus Malmström's Metal Cup: Comparing Maternal and Neonatal Outcomes - Wafaa M. Fageeh, (Journal of King Abdulaziz University: Medical Sciences, 2023)
With the introduction of the Kiwi OmniCup vacuum extractor at our institute, we aimed to evaluate and compare maternal and neonatal outcomes between the Kiwi OmniCup and the Malmström's metal cup in vacuum-assisted deliveries. A retrospective study on all women who delivered by vacuum extraction between November 2010 and April 2012 was conducted. We compared neonatal and maternal morbidity as well as the outcomes in the Kiwi and metal cup group by using chi-square tests. 202 women who had assisted-vaginal delivery (112 by Kiwi OmniCup and 90 by Malmström's metal cup) were included in this study. The mean Apgar scores at one and five minutes were lower in the metal cup group (P-value = 0.07 and 0.08, respectively). Thirty-nine newborns were admitted to the neonatal intensive care unit, of which 38 were discharged within one week. Eight of the 39 neonates were delivered by consultants versus 31 delivered by registrars (P-value = 0.039). There were no intrapartum or neonatal deaths. In conclusion, the Kiwi OmniCup is a safe alternative to the currently available Malmström's metal cup for vacuum assisted delivery.